2019
DOI: 10.1021/acsphotonics.9b00382
|View full text |Cite
|
Sign up to set email alerts
|

High-Efficient NUV Emission with Excellent Thermal Stability in Cd/Pb-Free AS-ZnO QDs by ALD without Surface Passivation

Abstract: Recently, near-ultraviolet (NUV)-emitting quantum dots (QDs) have attracted considerable attention for their potential in next-generation NUV-driven white-lightemitting diodes (with color rendering index >90). However, their widespread application in lighting products is greatly hindered by the inferior NUV-emitting efficiency, poor temperature stability, and toxicity of currently available Cd-/ Pb-containing QD systems. In the present work, we report the synthesis of ecofriendly Al 2 O 3 -surrounded (AS)-ZnO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…When the applied voltage is higher than V i , the device starts to emit light and a nonzero J L value will soon become the main current (i.e., J L > J R ) as the applied voltage further increases in a p–i–n lighting junction. It was found in our previous work , that a size reduction below the Bohr radius greatly enhances the quantum confinement effect, which eventually enhances the light emission. The ZSTs are 0.85, 1.02, and 1.19 nm in [5Z/10A] 11 , [6Z/10A] 10 , and [7Z/10A] 9 , respectively.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…When the applied voltage is higher than V i , the device starts to emit light and a nonzero J L value will soon become the main current (i.e., J L > J R ) as the applied voltage further increases in a p–i–n lighting junction. It was found in our previous work , that a size reduction below the Bohr radius greatly enhances the quantum confinement effect, which eventually enhances the light emission. The ZSTs are 0.85, 1.02, and 1.19 nm in [5Z/10A] 11 , [6Z/10A] 10 , and [7Z/10A] 9 , respectively.…”
mentioning
confidence: 72%
“…In the past, interface states were reported to often act as the quenching centers for the emissions, which led to nonradiative recombination, causing the system to be unfit for LEDs and solar cells . Recently, it has been found that visible photoluminescence (PL) intensity is dramatically enhanced by reducing the sublayer thickness of nanolaminates to be as small as the Bohr radius, attributed to the synergism of quantum confinement effects and interface states. ,, In compared with the photon-driven PL of nanolaminates, the electrically driven self-emissive nanolaminates are more feasible for realizing lighting LEDs as well as integrating into flexible electronic devices and microelectronic devices. It is well-known that LEDs require a multilayered structure with a charge injection layer, a charge transport layer, and a light-emitting layer to realize electroluminescence. , The gentle preparation conditions of light-emitting nanolaminates by atomic layer deposition (ALD) (e.g., low vacuum, low treatment temperature, and no postannealing process) are not only well compatible with the preparation process of the other layers, but also supply a great number of advantages for LEDs, such as low cost, good repeatability, flexibility, and nontoxicity.…”
mentioning
confidence: 99%
“…3). Alternatively, for Al 2 O 3 -surrounded ZnO quantum dots Li et al 45 reported an interface-related peroxide state Zn* that was shifted by 1.4 eV toward higher BE with respect to the Zn-O component; however, this finding is…”
Section: Paper Dalton Transactionsmentioning
confidence: 96%
“…Al 2 O 3 /ZnO bilayers (nanolaminates) and Al 2 O 3 -surrounded ZnO quantum dots prepared exclusively by thermal ALD (TALD) were studied by Chaaya et al 43 and Viter et al 44 as well as by Li et al 45 While these studies mainly addressed the structural and optical properties, we here focus preferentially on the interface electronic properties resulting from a mixed TALD and PEALD process.…”
Section: Introductionmentioning
confidence: 99%
“…Commonly used NIR-II probes include quantum dots (QDs) [ 19 ], organic dyes [ 20 ], single-walled carbon nanotubes (SWCNTs) [ 21 ], were often unsuitable for long-term in vivo fluorescent imaging, on accounting of inherent toxicity, short blood half-lives or poor biocompatibility. Furthermore, they also face challenges of photo-bleaching and reticuloendothelial system (RES) capture for the widespread adoption in clinical [ [22] , [23] , [24] ].…”
Section: Introductionmentioning
confidence: 99%